2017
DOI: 10.1002/jmv.24945
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diversity of rotavirus A genotypes cirulating in Turkey during a 2‐year sentinel surveillance period, 2014‐2016

Abstract: Human rotavirus A (RVA) is the main etiological agent of watery diarrhea among children under 5 years of age worldwide. The aims of this study were to investigate the prevalence and diversity of RVA genotypes circulating in Turkey during a 2-year sentinel surveillance study. A total of 1639 rotavirus antigen-positive stool samples were obtained from children younger than 5 years of age hospitalized with acute gastroenteritis. Rotavirus G and P genotypes were determined by reverse transcription polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
8
0
2
Order By: Relevance
“…Rotavirus was detected among children in all age groups. According to studies from different localities, it was found that rotavirus infection usually occurred in children younger than 3 years of age . In agreement with this, the finding revealed children less than 3 years of age (85.7%) had a higher rate of rotavirus infection than children over 3 years of age (13.3%), which children of the 12‐to‐23 month group (45.1%) being the most frequently affected.…”
Section: Discussionsupporting
confidence: 57%
“…Rotavirus was detected among children in all age groups. According to studies from different localities, it was found that rotavirus infection usually occurred in children younger than 3 years of age . In agreement with this, the finding revealed children less than 3 years of age (85.7%) had a higher rate of rotavirus infection than children over 3 years of age (13.3%), which children of the 12‐to‐23 month group (45.1%) being the most frequently affected.…”
Section: Discussionsupporting
confidence: 57%
“…Although these results do not reflect the society incidence, a decrease can be seen in G9 frequency (33). Also a rotavirus surveillance study from Turkey in 2014-2016 reported that the most prevalent genotype was G1P[8] (24.6%) followed by G3P [8] (19.6%) and G9P [8] (12.2%) (34). The samples of the present study belong to year 2012, which is one of the limitations of our study, however it can be seen from the literature that genotype G9 was the predominantly circulating genotype around 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışma süresinde ilk iki yılda görülmeyen G3P8 izolatının 2015 ve 2016 yıllarında sırasıyla %18.7, %13.5 oranlarında görüldüğü saptanmıştır. Durmaz ve arkadaşlarının yaptıkları sürveyans çalışmasının devamı niteliğindeki çalışmada 27 , bizim çalışmamızla uyumlu olarak 2014-2016 yıllarında G1P8 ve G3P8 izolatlarında artış ve G9P8, G2P4 izolatlarında azalma olduğu bildirilmiştir. Rotavirüs izolatlarının genotip dağılımındaki bu değişim, oluşan nokta mutasyonları ve hayvan izolatlarının insan izolatlarına olan etkisi sonucu yeniden ortaya çıkan genetik yapılanma nedeniyle gelişmektedir 28 .…”
Section: Discussionunclassified